Mixtures of herbicides on weed control in annual cotton - Nóbrega, Laudemiro B. da; Beltrão, Napoleão E. de M.; Azevedo, Demóstenes M. P. de; Vieira, Dirceu J. (Pesquisa Agropecuaria Brasileira, 2014)
A field trial was placed at Surubim, Pernambuco State, Brazil, in 1981, on a sandy medium soil to study the effect of several mixtures of herbicides against weeds in upland cotton (Gossypium hirsutum L). The experimental area had a balanced population of broad and narrow-leave weeds. The herbicides used were trifluralin, cyanazine, alachlor, pendimethalin, metolachlor, orizalin and diuron. The results showed that the cultivar tested SU 0450-8909 was resistant to the rate of herbicides and the mixtures were effective against weeds (mono and dicotyledonous). The most efficient broad and narrow-leave control was obtained by the mixtures alachlor + diuron (0.8 kg a.i/ha + 1.2 kg a.i/ ha), pendimethalin + diuron (1.2 kg a.i/ha + 1.2 kg a.i/ha) and metolachlor + diuron (1.8 kg a.i./ha + 1.2 kg a i/ha).